Peer Assisted Teaching Scheme : Final Report. - Carbone, Angela (Australian Learning and Teaching Council (ALTC), 2012)
Final report from a fellowship which aimed to achieve a consistent university-wide strategy to assist academics in improving units perceived by students as needing critical attention. This was accomplished by introducing a Peer Assisted Teaching Scheme (PATS). PATS integrates unit evaluation data with discipline-based academic development opportunities to build leadership capacity amongst academics. This builds on the current research that highlights the benefits of Peer Assisted Learning (PAL) programs and applies it to academic teaching staff. Specifically this fellowship was designed to: improve the quality of teaching and student satisfaction within identified units; and build leadership capacity amongst currently recognised outstanding teachers.